The Effect of Live Streaming and Sales Promotions on Impulse Buying Among Shopee Users in Semarang - Dwi Fatan Liliani; Widodo Widodo (Komunitas Dosen Indonesia, 2026)
This research seeks to examine how live streaming and promotional sales affect impulsive purchases by Shopee users in Semarang City. Employing a quantitative strategy through a survey, the research engaged 96 participants who were frequent Shopee users and had made impulse buys. The analysis was conducted using PLS-SEM with the SmartPLS software. The findings indicated that live streaming positively and significantly influenced impulse buying (O = 0.428; t = 3.181; p = 0.001), and sales promotions also had a notable and affirmative impact (O = 0.378; t = 2.757; p = 0.006). Together, these two independent factors accounted for 59.6% of the differences in impulse buying behaviour (R² = 0.596). These results emphasize that the quality of live streaming and the efficiency of sales promotions provided by Shopee are crucial in stimulating impulsive purchasing among consumers in today's digital marketing landscape. In addition, interactive content, real-time communication, and attractive promotional incentives appear to strengthen emotional engagement and urgency, encouraging spontaneous purchasing decisions. Therefore, optimizing live streaming features and promotional strategies can be considered an effective approach for e-commerce platforms to enhance consumer responsiveness and drive sales performance.